(untitled) (Pedagogical Horizons, 2022)
The aim of this article ist to illustrate the experience of graduates of the primary teacher training programme of the Private University of Education, Diocese Linz (PHDL) at their entry into their professional lives. Moreover, the article strives to give ideas on advancing the training programme and curriculum, and it should also contribute to bringing university and schools closer together. By means of qualitative research three aspects can be uncovered that are exemplary for beneficial framework conditions that support the professional development of new primary school teachers during their career entry.